Between assimilation and difference: The Constituent Assembly and indigenous territories - Kingman, Santiago (2008)
This article discusses the mechanisms used by Amazonian and highland indigenous communities in their effort to consolidate demands for political inclusion, within the context of the Constituent Assembly initiated in Ecuador in November 2007. The author analyses the way in which these mechanisms reveal distinct approaches to the concept of inclusion, itself a product of distinct historical and geographical experiences; and how the notion of inclusion oscillates between assimilation on the one hand, and differentiation on the other.